Cultural Relativism, Marxism, and Soviet Policy toward the Khanty - Bartels, Dennis (Culture, 1983)
The aims of this paper are fivefold: 1- to present data regarding some specific instances of conflict and change among the Khanty of western Siberia during the 1930’s; 2- to show that these changes cannot be evaluated from a cultural relativist point of view; 3- to evaluate these changes in light of a critique of cultural relativism recently proposed by Arthur Hippler; 4- to tentatively outline a Marxist critique of cultural relativism which is based on the ideas of several Soviet and Western anthropologists; and, 5- to evaluate changes among the Khanty during the 1930’s in light of this Marxist critique of cultural relativism.